Same karstic substratum, different aquatic communities? Case study: three water bodies from western Romania - CIORCA, Anca Mihaela; MOMEU, Laura; BATTES, Karina Paula (Studia Universitatis Babeș-Bolyai Biologia, 2017)
We investigated the phytoplankton, periphyton and microcrustacean communities developing on similar limestone substratum, in three karstic lakes: Iezerul Ighiel (Alba County), Dracului and Ochiul Beiului (Caraș-Severin County), during 2014 and 2016. Species richness was significantly higher in the lake greater in size for both algae and microcrustaceans, consistent with the species-area hypothesis. Forty algal taxa and only one microcrustacean species were common in all three lakes, even if comparable physico-chemical characteristics were recorded. Relatively similar saprobic conditions were shown by indicator species, while trophic state differed at some extent. Since current factors existing in the three environments were relatively similar (limestone substratum, physico-chemical parameters, water source etc.), the dissimilarities found in the plankton and periphytic communities were best explained by long-term factors like geographical isolation or the strength of disturbances.